Direct policy search for robust multi-objective management of deeply uncertain socio-ecological tipping points. (June 2017) - Quinn, Julianne D.; Reed, Patrick M.; Keller, Klaus
Abstract: Managing socio-ecological systems is a challenge wrought by competing societal objectives, deep uncertainties, and potentially irreversible tipping points. A classic, didactic example is the shallow lake problem in which a hypothetical town situated on a lake must develop pollution control strategies to maximize its economic benefits while minimizing the probability of the lake crossing a critical phosphorus (P) threshold, above which it irreversibly transitions into a eutrophic state. Here, we explore the use of direct policy search (DPS) to design robust pollution control rules for the town that account for deeply uncertain system characteristics and conflicting objectives. The closed loop control formulation of DPS improves the quality and robustness of key management tradeoffs, while dramatically reducing the computational complexity of solving the multi-objective pollution control problem relative to open loop control strategies. These insights suggest DPS is a promising tool for managing socio-ecological systems with deeply uncertain tipping points. Highlights: Managing socio-ecological systems with tipping points is a challenging multi-objective problem. Direct policy search (DPS) is a computationally efficient method for solving such problems. Compared to open loop control DPS finds policies that are more robust to deep uncertainties.